Insomnia is more common among subjects living in damp buildings. Issue 2 (18th January 2005) - Janson, C; Norbäck, D; Omenaas, E; Gislason, T; Nyström, L; Jõgi, R; Lindberg, E; Gunnbjörnsdottir, M; Norrman, E; Wentzel-Larsen, T; Svanes, C; Jensen, E J; et al.
Abstract : Background: Insomnia is a condition with a high prevalence and a great impact on quality of life. Little is known about the relation between and sleep disturbances and the home environment. Aim: To analyse the association between insomnia and building dampness. Methods: In a cross-sectional, multicentre, population study, 16 190 subjects (mean age 40 years, 53% women) were studied from Reykjavik in Iceland, Bergen in Norway, Umeå, Uppsala, and Göteborg in Sweden, Aarhus in Denmark, and Tartu in Estonia. Symptoms related to insomnia were assessed by questionnaire. Results: Subjects living in houses with reported signs of building dampness (n = 2873) had a higher prevalence of insomnia (29.4 v 23.6%; crude odds ratio 1.35, 95% CI 1.23 to 1.48). The association between insomnia and different indicators of building dampness was strongest for floor dampness: "bubbles or discoloration on plastic floor covering or discoloration of parquet floor" (crude odds ratio 1.96, 95% CI 1.66 to 2.32). The associations remained significant after adjusting for possible confounders such as sex, age, smoking history, housing, body mass index, and respiratory diseases. There was no significant difference between the centres in the association between insomnia and building dampness. Conclusion: Insomnia is more common in subjects living in damp buildings. This indicates that avoiding dampness in building constructions and improving ventilation in homes may possibly have a positive effect on the quality of sleep.